Analysis of Accusative and Genitive Cases in Juz 30 and Its Implementation in Nahwu Learning: Analisa Jar Majrur pada Juz 30 serta Implementasinya pada Pembelajaran Nahwu - Faujiyah, Faujiyah; Fauji, Imam (Universitas Muhammadiyah Sidoarjo, 2023)
This study delves into the pivotal role of human resources in advancing culture through effective language utilization and appreciation. Focusing on the concise verses of Juz 30 in the Quran, particularly the occurrence of Jar letters, the research investigates its implications for learning Nahwu. Employing a literature search and Quranic documentation, the study employs content analysis to identify 80 Jar letters from An-Naba to Al-Mutaffifin. The findings underline the significance of language proficiency in cultural development, revealing insights that can be harnessed in Nahwu education, thus fostering linguistic competence and cultural enrichment. Highlights: Significance of Language Appreciation: Emphasizes the pivotal role of language as a tool for cultural advancement and communication. Analyzing Jar Majrur in Juz 30: Investigates the occurrence of Jar letters in the concise verses of Juz 30 and its implications. Pedagogical Insights for Nahwu Learning: Identifies 80 Jar letters and their potential application in enhancing Nahwu education, contributing to linguistic competence and cultural enrichment. Keywords: Language Proficiency, Cultural Progress, Juz 30, Jar Majrur Analysis, Nahwu Learning